MUATAN DIMENSI PROFIL LULUSAN DALAM ANTOLOGI CERPEN TIUR DAN POLTAK DAN PEMANFAATANNYA SEBAGAI ALTERNATIF BAHAN AJAR SASTRA DI SMP NEGERI 11 MEDAN - Simanjuntak, Firman; Ansari, Khairil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the dimensi profil lulusan embedded within the short story anthology "Tiur dan Poltak," specifically focusing on the selected stories, while outlining their utilization as alternative literary instructional materials. Employing a descriptive design, this research gathered two primary types of data: (1) the inclusion of dimensi profil lulusan within the short stories' narratives and (2) the feasibility assessment of the instructional materials. The first data set was collected through a read-and-record technique using structured guidelines, followed by content analysis. Meanwhile, the validation of the instructional materials was obtained through written assessment instruments and structured interviews. The written assessments were analyzed by calculating the mean scores to determine feasibility levels, whereas the verbal validation was processed through qualitative analysis. The findings reveal that the selected short stories reflect the dimensi profil lulusan. Based on these results, the anthology was developed into a handout-style instructional material for reviewing fiction. The validation results, both written and verbal, demonstrate that the instructional materials are highly feasible for classroom implementation. This study is expected to serve as a scholarly reference for character-based literary analysis and the innovation of instructional materials in schools.